Sound insulation performance of sandwich structure compounded with a resonant acoustic metamaterial. (1st October 2021) - Lin, Qinhao; Lin, Qili; Wang, Yihang; Di, Guoqing
Abstract: To targeted regulate and improve the low-frequency sound insulation performances of traditional sandwich structures, a sandwich structure compounded with resonant acoustic metamaterial (SSCRAM) is proposed and an analytical model is established to evaluate its sound transmission loss (STL). The accuracy of the analytical model is verified by a simulation using finite element method and an experiment testing the sound insulation of a sample. Analytical results demonstrate that SSCRAM shows an excellent sound insulation performance in low frequency range. Compared with that of three other types of sandwich structures, an orthogonally rib-stiffened sandwich structure (ORSS), an ORSS with a perforated panel, and an ORSS with a plate-type acoustic metamaterial insertion, the STL of SSCRAM has an increment of 7.2 dB, 5.4 dB, and 7.9 dB in the frequency range of 370–670 Hz, respectively. By equating SSCRAM as a spring-mass model with two degrees of freedom and analyzing the distribution and dissipation of sound energy inside SSCRAM, the mechanism of sound absorption and insulation is clarified. Furthermore, the influences of six structure parameters on the sound insulation performance are quantitatively analyzed based on the analytical model, which can provide theoretical guidance for the targeted regulation of low-frequency sound insulation performance of SSCRAM in engineering applications.